A Prospective Observational Study on Impact of Clinical Pharmacy Services in the Management of Medications and Pharmaceutical Care in Geriatric Patients in a Tertiary Care Hospital - Radhakrishnan, Devika; Rego, Renee Lynn; S, Sanjana; D’Souza, Wilsita Snehal; Tom, Cyril (Indian Journal of Pharmacy Practice)
Aim: This research aims to evaluate how clinical pharmacy interventions affect patient outcomes, focusing on areas like patient counseling and pain management.Materials and Methods: This six-month prospective observational study was conducted at a tertiary care hospital, involving patients aged 60 and above. Customized questionnaires were used for patient counseling and pain management evaluation. Pain levels were assessed before and after discharge, and counseling was provided directly or through patient representatives when necessary. Results: Out of 132 patients, 63.64% received direct patient counseling, while 36.36% had their representatives counseled. Counseling sessions focused on educating patients about their medications, including their names, purposes, potential side effects, lifestyle modifications, and precautions. Improvement in physical activity, mobility, diet, mental health, and ensuring safety was seen post-counseling. Pain complaints were reported by 100 patients, in which the highest prevalence of pain was in females. 86% of patients depend on non-pharmacologic treatment. 66% of patients took analgesics, and most used was Tramadol. The mean pain score in NRS dropped significantly from 4.01 before management to 1.29 afterward with a higher pain satisfaction level. Conclusion: The study highlighted that clinical pharmacist involvement in geriatric care led to better medication management, fewer drug-related problems, and improved patient outcomes. Broader implementation of these services could further enhance care quality and reduce adverse events among elderly patients.
Keywords: Clinical Pharmacy Services; Geriatric Population; Patient Counseling; Pain Management